TUMBUHAN INANG dan POPULASI JUMLAH SARANG SEMUT RANGRANG (Oecophilla smaragdina) di HUTAN TAMAN WISATA ALAM BATUPUTIH KOTA BITUNG - Remina Wandik Remina Wandik; Terry M. Frans; Wawan. Nurmawan Wawan. Nurmawan (Universitas Sam Ratulangi, 2021)
ABSTRAKRangrang ants are one of the non-timber forest product commodities from the fauna group. Weaverants have the benefit of regulating ecological functions as decomposers and help pollinate floweringplants. Economically, weaver ant eggs are used for bird feed. The research was carried out in theBatuputih Nature Park Forest, Bitung City, North Sulawesi Province, for one month in March 2019. Thisstudy aims to determine the type of host plant and the population of the number of weaver ant nests inBatuputih TWA. The method used is a systematic strip sampling by recording all trees that have nests andpurposively to determine the sample. The results of the study showed that there were 14 (fourteen) typesof weaver ant host plants, namely sempur (Dillenia indica L) 57, forest walnut (Canarium littorale BI) 48,titolang (Gastonia serratifolia Miq.) 40, noni (Morinda Citrifolia L.) 33, wood egg (Alstonia angustifoliaWall.ex A. DC) 32, mamaling (Leea aculeate Blume) 29, ylang (Cananga odorata Lam) 19, waru(Hibicus tiliaceus L) 15, betel wood (Piper aduncum L) 12, banyan (Ficus benjamina L) 8, ganemo(Gnetum gnemon L) 7, flower wood (Spathodea campalunata P. Beauv) 3, white teak (Gmelina arboreaRoxb) 1, and seho yaki (Caryota mitis Lour) 4. Average number of nests / species host plant, sempur 6.33nests, forest walnut 8 nests, titolang 6.6 nests, noni 6.6 nests, egg wood 5.3 nests, mamaling 5.8 nests,ylang ylang 4.7 nests, waru 15 nests, wood 4 nests of betel, 8 nests of banyan, 3.5 nests of ganemo, 3nests of flower wood, 1 white teak, 1.3 nests of seho yaki.Keywords: weaver ants, host plant species, non-timber forest products, batuputih natural tours park.